Influence Factors Social and Cultural Rights on the Evolution of Management Accounting - SIMIONESCU, Silvia; BICĂ, Elena (Journal of Advanced Research in Management; Vol 7 No 2 (2016): JARM Volume VII Issue 2(14) Winter 2016, 2017)
Looking to understand management accounting in competitive environments and advanced technologies, changing has become increasingly an area of research. Many firms have been significant changes in organizational and competitive technologies. As they change management challenges answered the question arose of choosing the most effective techniques and management methods. Management organizations face the challenge of strengthening managerial accounting system, to choose strategies and methods that work together in order to obtain a competitive advantage and enhance performance.